EFEKTIVITAS PENGELOLAAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PENDIDIKAN DAN TENAGA PENDIDIKAN - Hutapea, Rotua Sriyanti; Siregar, Astri Novia; Irvan, Irvan (Hijri, 2023)
This research aims to determine the effectiveness of human resource management in improving the performance of educators and education staff. This research was carried out from December 2022 - April 2023. Using data collection techniques observation, interviews, documentation and data analysis techniques by reducing data and drawing conclusions . The results of the research show that the human resource management recruitment process in teacher recruitment at SMA Negeri 1 Sei Bamban is carried out starting from the preparation stage with evaluation and analysis of teacher conditions carried out by the principal and representatives of the school curriculum, the data collection stage by analyzing the required teacher positions and other needs related to this, preparation stage, data collection stage, curriculum determination stage, program planning stage, implementation of needs planning for teacher readiness to be carried out or recruitment and selection of teachers who can be empowered to fill non-urgent and vital subjects, planning stage program by creating a teacher procurement program and coaching the creation of teaching equipment, and the implementation stage of teaching staff planning. The implementation of human resource management at SMA Negeri 1 Sei Bamban can be seen from: First, namely the placement of human resources, the placement of human resources at SMA Negeri 1 Sei Bamban is in accordance with the educational background and competencies possessed by an educator, namely in accordance with the main tasks and desires of the educator, second, teacher performance management is carried out by providing or holding training and coaching through MGMP. Third, performance assessment is carried out by the school principal by looking at teacher performance during the learning process both inside and outside the classroom, as well as providing supervision of each teacher and check the attendance list of an educator